2011
DOI: 10.1024/0301-1526/a000081
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tissue factor and microparticles are not increased in patients with deep vein thrombosis

Abstract: Circulating TF and microparticles are not elevated in deep venous thrombosis. The increase in IL-6, IL-8 and F1 + 2 during thrombosis was not proportional to the extent or predisposing risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Several cross sectional studies have reported increased MP procoagulant functional activity [98, 99], while others have shown increased MPs by FCM [90, 99102]. Still other studies failed to demonstrate an increase in MPs, either using functional assays [103105] or FCM [106, 107]. Again, these contradictory results are most likely attributable to differences in methodologies and techniques.…”
Section: Phenotypic Vs Functional Assays For Microparticle Analysismentioning
confidence: 99%
“…Several cross sectional studies have reported increased MP procoagulant functional activity [98, 99], while others have shown increased MPs by FCM [90, 99102]. Still other studies failed to demonstrate an increase in MPs, either using functional assays [103105] or FCM [106, 107]. Again, these contradictory results are most likely attributable to differences in methodologies and techniques.…”
Section: Phenotypic Vs Functional Assays For Microparticle Analysismentioning
confidence: 99%
“…42,43 Several, but not all studies, found that either plasma TF-MP concentration or TF-MP procoagulant activity positively correlates with the risk of VTE. 41,[43][44][45][46] An explanation for these inconsistent findings may be that detection of MPs is often inaccurate because of their small size. With regard to the recurrence of VTE, a clearer picture emerges.…”
mentioning
confidence: 99%
“…Studies evaluating the role of MP-TF in the pathophysiology of VTE in the general (non-cancer) population are scarce and so far no study specifically addressed its association with recurrent VTE. Two previous studies reported that MP-TF activity was not increased in patients with a first manifestation of acute VTE compared to control patients [ 13 , 32 ]. In contrast, Ye et al did observe higher monocyte-derived MP-TF levels and MP-TF activity in patients with an acute episode of first or recurrent DVT compared with healthy controls although this study comprised only 50 patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%